Antibacterial Effect of Ethanol Extracts of Murraya paniculata Leaves, Smallanthus sonchifolius Leaves, Apis trigona Honey, and their Combination Against Staphylococcus epidermidis - Kusuma, Sri Agung Fitri; Herawati, Irma Erika; Nugrahaningtiyas, Felika (Chimica et Natura Acta, 2025)
Several studies have reported that combining plant extracts may enhance their efficacy against specific bacterial infections. This study aimed to analyze the antibacterial interaction of ethanol extracts of Murraya paniculata leaves, Smallanthus sonchifolius leaves, Apis trigona honey, and their combinations against Staphylococcus epidermidis ATCC 12228, as each component has shown individual antibacterial activity against this bacterium. The antibacterial interactions of the test materials, both individually and in combination, were evaluated using the agar diffusion method with clindamycin phosphate as the standard antibiotic. The minimum inhibitory concentration (MIC) of the most potent extract was determined through the microdilution method according to the Clinical and Laboratory Standards Institute (CLSI) guidelines, while the minimum bactericidal concentration (MBC) was assessed via subculture on solid media. Among all tested substances, the S. sonchifolius leaf extract exhibited the highest antibacterial activity, with similar MIC and MBC values ranging from 15.625 to 31.25 mg/mL. Interaction tests revealed a significant difference, showing that the combination of all three agents had an antagonistic effect, whereas the combination of both leaf extracts produced a synergistic antibacterial effect. However, the inhibitory effect of the combination was not greater than that of the yacon extract alone. In conclusion, S. sonchifolius leaf extract demonstrates strong potential as a single antibacterial agent against S. epidermidis.